Facial Expression as Emotional Diagnostic (FEED): New Opportunities for Tourism and Hospitality (A Literature Review) - Maresville, Charlotte De Sainte; PETR, Christine (E-Journal of Tourism, 2024)
Facial expressions can be used to understand the emotional needs of tourist travelers. Interpreting facial expressions allows for customizing offers, enhancing emotional engagement, and obtaining customer evaluations. To guide stakeholders in the tourism industry in effectively integrating this technology, this article presents the potential of using facial expressions in tourism. The present approach (Facial Expression as Emotional Diagnostic: FEED) consists of 4 steps: 1) emotional diagnosis, 2) pre-experience customization, 3) emotional engagement during the experience, and 4) customer satisfaction measures. By distinguishing between online and offline situations, we unfold these 4 steps of the FEED process. Further research will address associated technical and ethical challenges, including algorithmic biases and privacy concerns.